African economic outlook. - African Development Bank.; Organisation for Economic Co-operation and Development (Paris, France : African Development Bank : Development Centre of the Organisation for Economic Co-operation and Development, 2002)
The African Economic Outlook combines the development expertise of the OECD, with the knowledge of the African Development Bank on African economies. The objective is to review annually the recent economic situation and the short-term likely evolutions of selected African countries. The Outlook is drawn from a country-by-country analysis based on a unique analytical design. This common framework includes a forecasting exercise for the current and the two following years using a simple macroeconomic model, together with an analysis of the social and political context.
Library has 2003/2004 in English and French
opc 08/09/16
Ref.
Keywords: Economic situation; Afrika; Economic history; Economic policy; Africa